Public Service Announcement (2D) - Insomnia (Sleep Disorder) - Rosnas Syazwana Zakaria,; Roslinawati Jaafar, (Journal of Computing Technologies and Creative Content, 2022)
Insomnia may be described as “continual problem with sleep initiation, duration, consolidation or quality”. The remedies which have been practiced in treating insomnia consisting of cognitive behavioural therapy (CBT), stimulus control therapy, and mild therapy. Nowadays, Insomnia is a not unusual place in public health trouble and the superiority and effect of insomnia in number one care attendees is now no longer nicely documented withinside the Asian populace. To enumerate, primarily based totally on statistical studies In Malaysia, 33.8% of the overall populace have been said to have insomnia signs and symptoms and 12.2% had continual insomnia. However, the goal of this study is to introduce 2D Animation Public Service Announcement (PSA) as an opportunity cognizance for Insomnia sufferers. The goal of this task is are to show public approximately Insomnia (sleep disorder) the usage of Public Service Announcement, to produce a 2D Animation Public Service Announcement on Insomnia (sleep disorder). The 2D Animation Public Service Announcement could be in Bahasa Melayu for a few humans do now no longer recognize in international language. It is desire that this 2D Animation Public Service Announcement will successfully act as an opportunity device in Insomnia (sleep disorder) remedy with the aid of using assuring a secure surroundings aspect wherein the state of affairs may be managed with the aid of using consumer and thus, specializes in the attention of Insomnia (sleep disorder). This task uses Adobe Illustrator and Adobe After Effect as software program of 2D Animation.  This task used ADDIE Method which is Analysis, Design Development, Implementation and Evaluation.